Phosphoproteomic Analysis Reveals Downstream PKA Effectors of AKAP Cypher/ZASP in the Pathogenesis of Dilated Cardiomyopathy - Lv, Jialan; Pan, Zhicheng; Chen, Jian; Xu, Rui; Wang, Dongfei; Huang, Jiaqi; Dong, Yang; Jiang, Jing; Yin, Xiang; Cheng, Hongqiang; Guo, Xiaogang (Frontiers in Cardiovascular Medicine, 2021)
Background: Dilated cardiomyopathy (DCM) is a major cause of heart failure worldwide. The Z-line protein Cypher/Z-band alternatively spliced PDZ-motif protein (ZASP) is closely associated with DCM, both clinically and in animal models. Our earlier work revealed Cypher/ZASP as a PKA-anchoring protein (AKAP) that tethers PKA to phosphorylate target substrates. However, the downstream PKA effectors regulated by AKAP Cypher/ZASP and their relevance to DCM remain largely unknown. Methods and Results: For the identification of candidate PKA substrates, global quantitative phosphoproteomics was performed on cardiac tissue from wild-type and Cypher-knockout mice with PKA activation. A total of 216 phosphopeptides were differentially expressed in the Cypher-knockout mice; 31 phosphorylation sites were selected as candidates using the PKA consensus motifs. Bioinformatic analysis indicated that differentially expressed proteins were enriched mostly in cell adhesion and mRNA processing. Furthermore, the phosphorylation of β-catenin Ser675 was verified to be facilitated by Cypher. This phosphorylation promoted the transcriptional activity of β-catenin, and also the proliferative capacity of cardiomyocytes. Immunofluorescence staining demonstrated that Cypher colocalised with β-catenin in the intercalated discs (ICD) and altered the cytoplasmic distribution of β-catenin. Moreover, the phosphorylation of two other PKA substrates, vimentin Ser72 and troponin I Ser23/24, was suppressed by Cypher deletion. Conclusions: Cypher/ZASP plays an essential role in β-catenin activation via Ser675 phosphorylation, which modulates cardiomyocyte proliferation. Additionally, Cypher/ZASP regulates other PKA effectors, such as vimentin Ser72 and troponin I Ser23/24. These findings establish the AKAP Cypher/ZASP as a signalling hub in the progression of DCM.